Improving the Results of Basic Running Movements Through Traditional Games Based on Discipline and Cooperation in Physical Education Learning - Delfin Masna Gulo; Darma Setiawan (Journal Physical Health Recreation (JPHR), 2023)
The aim of this research is to improve the results of basic running movements by playing traditional games with students at State Elementary School 060878. This research uses the Classroom Action Research (PTK) method. The subjects of this research were 30 students. Based on the research results, there were results for improving basic running movements in students at State Elementary School 060878. Before being given complete action, the results of basic running movements at the Pre-Cycle stage with good grades were 12 students or 40%. then given actions with traditional games for basic running movements in cycle I, the results of basic running movements were completed with a good score of 15 students or 50%, then given more actions with traditional games for the results of basic running movements in cycle II stage, achieving completeness for 8 students with Very good marks and 15 students got good marks. So those who have reached the KKM are 23 students or 77%.